Breeding, Healthcare and Marketing Practices of Goat Followed in Middle Gujarat - Jegoda, Mahendra N; Belsare, Vijay P (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A study was conducted in selected areas of Dahod and Kheda districts of Middle Gujarat to ascertain the breeding, health care and marketing management practices followed by goat keepers. The data was collected from randomly selected 240 goat keepers through personal interview with the help of pre-tested structured interview schedule. The study revealed that majority of goat keepers (96.67%) followed a flock mating system and bred their goat throughout the year (58.75%) by use of own flock buck (72.92%). More than two third of goat keepers (67.08%) followed some controlled breeding criteria in a flock and more than half of the respondents (56.67%) selected the breeding buck based on physical characteristics. About 57.50 % of goat keepers practiced estrus symptoms in doe, viz., frequent bleating and buck-doe seeking behavior followed by tail wagging and mounting on another goat (42.50%). Only one fifth (20.0%) of goat keepers implemented to vaccinate their adult goats and majority of goat keepers (77.08%) got treated their sick goats by local quack or used home-made remedy and least treated by veterinary doctors. Majority of goat keepers (65.42%) isolated the sick goats from healthy flock and 74.58% practiced the disposal of placenta on thorny hedge or tree. Most goat keepers (70.42%) sold adult does/bucks and male youngsters from the flock to raise money for their families throughout the year, and they marketed adult goats when they were between 12 and 18 months old (72.50%) to increase their selling price based on the body weight and age of the goat (75.0%). Most goat keepers (98.75%) sold their goats straight into the local market (haat) (65.83%) during the festive season, followed by 34.17% who sold to middlemen or villagers’ residents. The optimal breeding season was less common in the Kheda district, and there were disparities between districts more in the regulated (controlled) breeding practises, breeding buck selection criteria, isolation of sick goats, and goat marketing channels.